On a new species of Moniezia babai Blanchard, 1891(Cestoda: Anoplocephalidae) from Capra hircus (L.) from Buldhana district (M.S.) India - Borde2, *Atul Humbe1, Swati Jadhav2 and Sunita (International Multidisciplinary Research Journal, 2011)
The present communication deals with a new species of the genus Moniezia Blanchard, [2] from the intestine of Capra hircus (L.) at. Chikali District Buldhana (M.S.) India. The new species Moniezia babai Sp.Nov is characterized by the presence of scolex globular, elongated, mature proglottids four times broader than long, testes small in size, rounded scattered posterior to segment, 190-220 in numbers, cirrus pouch oval, ovary compact, rounded, vitelline gland post ovarian.